Therapeutic Management of a Downer Cow – A Case Report - Rahman, Mustafizur; Sarma, Ranjit; Islam, Rafiqul (International Journal of Livestock Research, 2019)
A six-year-old Sahiwal cow of Instructional Dairy Farm in the Department of Animal Husbandry and Dairying, SCS College of Agriculture, AAU showed a symptom of lateral recumbency and subnormal temperature. It was a dystotic cow and unable to lift the hind part after 8 hours post calving. Complete loss of appetite was observed leading to severe dehydration. Prognosis was found to be poor. Little response was observed when treated with calcium and magnesium borogluconate. Even after several attempts the cow failed to stand up. The characteristic crawling with the forelimb resulted in the development of wounds in various regions viz. knees, shoulder, brisket, tuber coxae and thighs. A combination of therapy and physical management could save the life of the Sahiwal cow and complete recovery was noticed after 35 days.